2018
DOI: 10.21079/11681/30369
|View full text |Cite
|
Sign up to set email alerts
|

Mississippi river bedform roughness and streamflow conditions near Vicksburg, Mississippi : data collection summary and analysis

Abstract: Bedforms are a consequence of flow of sufficient magnitude over a mobile sediment bed. They are a primary component of the drag acting upon a moving stream, yet are infrequently explicitly treated in numerical models of fluvial sediment transport. This study aims to document the collection of bathymetric data in the Mississippi River in an area of persistent and dynamic bedforms over a range of flow conditions, statistically examine bedform geometry, and parameterize results for inclusion in numerical models. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…These results are in contrast with the theoretical findings of M. S. and Van Rijn (1984) for dunes in equilibrium whereby it is found that dune wavelength is mainly controlled by the water depth. However, these trends are confirmed by the analysis with an alternative method conducted by Ramirez et al (2018) for the same flows that is, the heights and wavelengths for the same locations were 1.44 and 80.1 m for the low flow and 3.1 and 64.5 m for the high flow, respectively. As expected, the differences between the bed geometries for the two flows result in commensurate differences between the transported sediment (see Figures 4g and 4h).…”
Section: Case Study: Amv Applied To In-situ Mbes Measurementsmentioning
confidence: 65%
See 4 more Smart Citations
“…These results are in contrast with the theoretical findings of M. S. and Van Rijn (1984) for dunes in equilibrium whereby it is found that dune wavelength is mainly controlled by the water depth. However, these trends are confirmed by the analysis with an alternative method conducted by Ramirez et al (2018) for the same flows that is, the heights and wavelengths for the same locations were 1.44 and 80.1 m for the low flow and 3.1 and 64.5 m for the high flow, respectively. As expected, the differences between the bed geometries for the two flows result in commensurate differences between the transported sediment (see Figures 4g and 4h).…”
Section: Case Study: Amv Applied To In-situ Mbes Measurementsmentioning
confidence: 65%
“…This morphing appears to be driven by secondary dunes translating over the primary, larger, dunes according to Ramirez et al. (2018). Along channel bedform profiles at the same location for both flowrates are illustrated in Figures 3c and 3d.…”
Section: Case Study: Amv Applied To In‐situ Mbes Measurementsmentioning
confidence: 92%
See 3 more Smart Citations